MINIMASI KECEPATAN PROSES PEMILAHAN SAMPAH DAUR ULANG MELALUI PERBAIKAN TATA LETAK FASILITAS DI BANK SAMPAH MAJU SEJAHTERA - Ramses G Tandi Salu; Tritiya A R Arungpadang; Jefferson Mende (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2023)
Maju Sejahtera Waste Bank is a waste processing industry in Manado City and is managed directly by the Malalayang District government which was established in 2021. This research aims to find out the process of sorting recycling waste and make improvements to the layout of waste bank facilities using Promodel Software. Research was carried out at the Maju Sejahtera Waste Bank and data collection in the form of interviews with managers and workers of the waste bank and conducted direct observations to calculate the time of waste transport vehicles and documentation. The results showed that the layout of the facility in the initial layout and the simulated proposal layout had a significant difference from the results of the simulations carried out. Keywords: Waste Bank, Facility Layout, Software Promodel.